AN ANALYSIS OF BULLYING BEHAVIOR AMONG ADOLESCENTS IN MAKASSAR CITY - Aryani, Farida; Saman, Abdul; Kaffah, Muhammad Silmi (JURNAL NALAR PENDIDIKAN, 2025)
Bullying is a common issue among adolescents. This study analyzes bullying behavior in Makassar City using a descriptive quantitative method. The population includes all junior high school students, with a sample of 317 respondents who completed a questionnaire via Google Forms. Data were analyzed using univariate analysis. Results showed that most respondents were female (204 of 64.4%), with the majority aged 14. bullying remains prevalent, emphasizing the crucial role of school counselors and the school community in prevention and intervention efforts.